Brucella sp. sequence‑type 27 associated with abortion in dwarf sperm whale Kogia sima - Hernández-Mora, Gabriela; González-Barrientos, Rocío; Víquez‑Ruíz, Eunice; Palacios Alfaro, Jose David; Bettoni‑Rodríguez, Gianmarco; Gendre, Marlène; Vincent, Charline; Roca‑Monge, Karol; Ruiz-Villalobos, Nazareth; Suárez-Esquivel, Marcela; Cordero‑Chavarría, Minor; Chaves-Olarte, Esteban; et al. (European Journal of Wildlife Research, 2021)
A dwarf sperm whale Kogia sima stranded alive along the Central Pacifc Coast of Costa Rica. The whale, handled by tourists and local inhabitants, was weak, had buoyancy difculties, and eventually aborted and died, showing severe necrotizing placentitis and other pathological signs. Both the mother and the fetus had antibodies against Brucella lipopolysaccharide. Brucella organisms were isolated from various tissues of both animals and were characterized. The bacterium genome corresponded to sequence-type 27 (ST27) and clustered together with other Brucella ST27 isolated in humans and cetaceans. Un cachalote enano Kogia sima varó vivo en la costa del Pacífico Central de Costa Rica. La ballena, manipulada por los turistas y los habitantes de la zona, estaba débil, tenía problemas de flotabilidad y finalmente abortó y murió, mostrando una grave placentitis necrotizante y otros signos patológicos. placentitis y otros signos patológicos. Tanto la madre como el feto tenían anticuerpos contra el lipopolisacárido de Brucella. Se aislaron organismos de Brucella de varios tejidos de ambos animales y se caracterizaron. El genoma de la bacteria correspondía al tipo de secuencia 27 (ST27) y se agrupaba con otras Brucella ST27 aisladas en humanos y cetáceos. Universidad Nacional, Costa Rica Escuela de Medicina Veterinaria